R. N. MACEDONIA AND THE CFSP OF THE EUROPEAN UNION: ACHIEVEMENTS AND CHALLENGES (Annual of the Faculty of Philosophy in Skopje, 2019)
Three determinants shape the role and influence of the EU as a global-regionalactor in peace and security: capacity (institutional, material, human and operational,as well as financial) to undertake missions; willingness to devote resources tosecurity and defence purposes, mainly driven by member states’ priorities; and acceptance(internal and external) of the EU as a leading actor in peace and security.The institutional security and defence framework of the EU has undergone many reformsin the past three decades. The beginnings of this process have been establishedby the Treaty of Maastricht (1992) that has established the EU Common Foreignand Security Policy (CFSP). By the Stabilization and Association Agreement enteringinto force, R.N. Macedonia has officially confirmed its determination for movingcloser to the CFSP goals. Therefore, the paper analyses the process that R.N. Macedoniais implementing regarding this issue, as well as it faced challenges.
Keywords: EU; CFSP; SAP; MACEDONIA